Evidence of gene orthology and trans‐species polymorphism, but not of parallel evolution, despite high levels of concerted evolution in the major histocompatibility complex of flamingo species. (23rd December 2015) - Gillingham, M. A. F.; Courtiol, A.; Teixeira, M.; Galan, M.; Bechet, A.; Cezilly, F.
Abstract: The major histocompatibility complex (MHC) is a cornerstone in the study of adaptive genetic diversity. Intriguingly, highly polymorphic MHC sequences are often not more similar within species than between closely related species. Divergent selection of gene duplicates, balancing selection maintaining trans‐species polymorphism (TSP) that predate speciation and parallel evolution of species sharing similar selection pressures can all lead to higher sequence similarity between species. In contrast, high rates of concerted evolution increase sequence similarity of duplicated loci within species. Assessing these evolutionary models remains difficult as relatedness and ecological similarities are often confounded. As sympatric species of flamingos are more distantly related than allopatric species, flamingos represent an ideal model to disentangle these evolutionary models. We characterized MHC Class I exon 3, Class IIB exon 2 and exon 3 of the six extant flamingo species. We found up to six MHC Class I loci and two MHC Class IIB loci. As all six species shared the same number of MHC Class IIB loci, duplication appears to predate flamingo speciation. However, the high rate of concerted evolution has prevented the divergence of duplicated loci. We found high sequence similarity between all species regardless of codon position. The latter is consistent with balancing selection maintaining TSP, as under this mechanism amino acid sites under pathogen‐mediated selection should be characterized by fewer synonymous codons (due to their common ancestry) than under parallel evolution. Overall, balancing selection maintaining TSP appears to result in high MHC similarity between species regardless of species relatedness and geographical distribution.